Variational approach to the confined hydrogen atom with a moving nucleus - Fernández, Francisco Marcelo (2012)
We calculate the ground-state energy and other physical properties of the hydrogen atom inside a spherical box with an impenetrable wall. We apply the variational method and show that the total, kinetic, and potential energies for the moving nucleus model are greater than those for the case in which the nucleus is clamped at the box center.